Bond Strength Between Resin Cement to High-Translucency Zirconia Following Sandblasting And Non-Thermal Plasma Treatment - Silva, Daniele Oliveira da; Sato, Tabata Prado; Silva, Marina Bacelar; Souza, Letícia Grilo de; Uemura, Eduardo Shigueyuki; Silva, João Mauricio Ferraz da (Brazilian Dental Science, 2020)
Objective: The aim of this study was to compare the bond strength of High-Translucency zirconia (HT) and lithium disilicate dental ceramics, under different surface treatments. Material And Methods: For this, ceramics were divided into groups: Control Group (C) (n = 5), lithium disilicate sheets, conditioned with 10% hydrofluoric acid, followed by application of 37% phosphoric acid, silane and universal adhesive application; Group HTAI (n = 5), HT zirconia sheets were blasted with silica oxide, followed by the application of universal adhesive; Group HTPAI (n = 5), HT zirconia sheets were blasted with silica oxide, followed by the application of non-thermal plasma and universal adhesive and the HTP Group (n = 5), HT zirconia received only the application of non-thermal argon plasma. Subsequently, the specimens of each group were subjected to a cementation process with resin cement, obtaining cylinders. After 24 h of storage, in distilled water, at 37°C, the specimens were subjected to a mechanical micro-shear test. The data obtained were submitted to ANOVA One-way followed by the Tukey test (5%). Results: The HTP Group was excluded from the statistical analysis, as adhesions failed within the storage period. In addition, it was not possible to verify a statistical difference between the control group C and the experimental groups HTAI and HTPAI. Conclusion: The results showed that the applicability of high translucency zirconia can potentially be compared to the lithium disilicate bond strength, when submitted to the same surface treatments, except for the plasma application, which alone was not effective. KEYWORDS Lithium disilicate; Nonthermal plasma; Zirconia ceramic.